Future of CV Medicine - Mosley, Mary (MD Conference Express, 2015)
Computer-based design and modeling and the emerging field of physiomimetics are bringing forth changes to the practice of clinical cardiology, such as personalized prosthetic valves and a virtual fractional flow reserve clinical tool, and to pharmaceutical research and development. The personalized valves are produced by 3D printing using computer-aided design.